Project Report on Voice Over Internet Protocol - KIRAN G,NATARAJ,KRISHNAMURTHY and MAHESH K S (2006)
INTERNAL GUIDE: SHANTA KUMAR B PATIL MVJCE EXTERNAL GUIDE: DEVADUTT PROJECT MANAGER PACIFIC IT SOLUTIONS
Keywords: Voice Over Internet Protocol